Cat Kid Comic Club - Book 1 - Pilkey, Dav, 1966- (New York, NY : Graphix,. an imprint of Scholastic, 2020)
A brand-new graphic novel series by Dav Pilkey, the internationally bestselling author and illustrator of the Dog Man and Captain Underpants series. Readers of all ages will unleash their own creativity as they open the door to visual comic-book storytelling with the help of Dav Pilkey and his heartfelt, humorous, and amazing cast, featuring Li'l Petey, Molly, and Flippy in Cat Kid Comic Club.
Keywords: Cats -- Comic books, strips, etc; Persistence -- Comic books, strips, etc; Clubs -- Comic books, strips, etc; Composition (Language arts) -- Comic books, strips, etc; Drawing -- Comic books, strips, etc; Cats -- Fiction; Persistence -- Fiction; Clubs -- Fiction; Composition (Language arts) -- Fiction; Drawing -- Fiction; Comics (Graphic works); Humorous comics; Children's stories -- Comic books, strips, etc